MOHAMMAD HATTA AND RELIGIOUS-NATIONALISM EDUCATION IN BANDA EXILE - Renyaan, Kasman (Erudio Journal of Educational Innovation, 2024)
This article describes the thinking and consistency of a figure of the National Movement, Mohammad Hatta, during his exile in Banda Naira in 1963–1942. Research uses historical methods through heuristic, critical, interpretative, and historiographic stages. The main sources used were the work of the historian's books, other reference books, observations of objects in the house of his exile, and interviews with Banda Naira people. The study found that Mohammad Hatta, during Banda Naira's exile, remained critical (non-cooperative) of colonial policy. Hatta's routine on the spice island is filled with various activities to educate the community and the young generation of Banda, ranging from reading, writing, sports, attending public wedding invitations, speaking in mosques, forming youth organizations (PERBAMU), to playing the role of setting up the "School of Sore," which teaches many things about humanity, socialism, democracy, religion, morals, patriotism, and nationalism. Mr. Hatta's educational style has opened a veil of backwardness and stupidity to the Banda children, who live under the influence of Dutch hedonism. Hatta's thoughts, actions, and ignorance have shaped new knowledge for the generation of Banda. Traditional and Islamic religion in Banda Naira also influenced Hatta's mind to find the concept of building an independent Indonesia. As a legacy of Hatta's religious values and national spirit, the Banda community named the two people on the island (Hatta Island and Sjahrir Island), as well as a mosque called Hatta-Sjahrir in Banda Naira.